Composite sodium iron sulfate analog positive electrode material and preparation method thereof, positive electrode and sodium ion battery
By using modified carbon-based microspheres in sodium ion batteries to react hydrothermal with sulfate ions and sodium ions, a sodium ferrosulfate coating is formed, which solves the dissolution problem of sodium ferrosulfate under acidic conditions and improves the battery Cycling performance and capacity retention simplify the preparation process.
Patent Information
- Application Number
- CN202411377086.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The polyanionic material sodium sulfate in sodium ion batteries causes Fe3+ dissolution and uneven deposition of sodium dendrites under acidic conditions during the synthesis process, resulting in battery capacity attenuation and short circuit problems.
Modified carbon-based microspheres are used as templates, and a modifier with chelating ability to ferrous ions is hydrothermal reaction with sulfate ions and sodium ions in a solution with pH ≤3 to form a sodium ferrous sulfate coating. Avoid dissolution of the positive electrode material under high voltage electrical conditions, and ensure spherical shape and performance through the water-in-oil microemulsion droplet structure.
The high conductivity and ferrous ion capture capability of the cathode material are achieved, the cycle performance and capacity retention of the battery are improved, and the preparation process is simplified without sintering.
Smart Images

Figure CN118908288B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cathode material preparation, and in particular to a composite sodium iron sulfate analog cathode material and a preparation method thereof, a cathode and a sodium ion battery. Background Art
[0002] Sodium ion batteries are batteries that use layered oxides (such as nickel iron manganese oxide and copper iron manganese oxide) materials, Prussian blue analogs (such as iron-based Prussian white, etc.), polyanions (such as sodium iron sulfate, sodium iron phosphate, etc.) as positive electrodes, and carbon materials (such as hard carbon, soft carbon) as negative electrodes. They mainly use esters and ethers as solvents. + Metal salts (such as sodium fluoride salts, sodium borate salts and perchlorates) electrolytes and various additives (such as film-forming, flame retardant and overcharge protection) form an electrolyte. Although polyanion materials (sodium iron sulfate) have the advantages of low cost, high safety and long cycle life, the synthesis process is mostly acidic, resulting in the strong acidity of the sodium iron sulfate material itself and the Fe 3+ The dissolution of sodium has become two inevitable problems, and the uneven deposition of sodium dendrites has accelerated the capacity decay and short circuit of the battery.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a composite sodium iron sulfate analog positive electrode material and a preparation method thereof, a positive electrode and a sodium ion battery, aiming to improve at least one of the problems mentioned in the background technology.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a method for preparing a composite sodium iron sulfate analog positive electrode material, comprising:
[0007] Obtaining modified carbon-based microspheres, wherein the modified carbon-based microspheres are carbon-based microspheres loaded with a modifier having chelating ability for ferrous ions;
[0008] The modified carbon-based microspheres are mixed with sulfate ions, ferrous ions and sodium ions in a solution system with a pH of ≤ 3 to obtain a turbid solution;
[0009] The turbid liquid is mixed with a cationic surfactant and an oily organic solvent to obtain an emulsion, and then the emulsion is subjected to a hydrothermal reaction at 130-160° C. to allow sulfate ions, ferrous ions and sodium ions to fully react to generate sodium ferric sulfate that is coated on the surface of the modified carbon-based microspheres;
[0010] extracting a solid product from the mixed system after the hydrothermal reaction is completed;
[0011] The boiling point of the modifier is higher than the temperature of the hydrothermal reaction;
[0012] The carbon-based microspheres are activated carbon microspheres with a specific surface area of 500~1000m 2 / g.
[0013] In an optional embodiment, the invention includes the following features (1) or (2):
[0014] (1) The modifier has a group capable of chelating ferrous ions, and the group is selected from at least one of cyano, thiazole, amine and imidazole;
[0015] (2) The modifier is selected from at least one of cimetidine, thiazolidine and nizatidine.
[0016] In an optional embodiment, the method for obtaining modified carbon-based microspheres comprises:
[0017] The modifier is dissolved in a solvent to obtain a modifier solution, and the carbon-based microspheres are immersed in the modifier solution so that the modifier is adsorbed on the carbon-based microspheres; then, solid-liquid separation is performed to obtain modified carbon-based microspheres.
[0018] In an optional embodiment, at least one of the following features (1) to (3) is included:
[0019] (1) The particle size of carbon-based microspheres is 2~3μm;
[0020] (2) The concentration of the modifier solution is 1~5g / mL;
[0021] (3) The solvent for dissolving the modifier is at least one selected from diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate.
[0022] In an optional embodiment, at least one of the following features (1) to (5) is included:
[0023] (1) the cationic surfactant is at least one selected from the group consisting of dodecyltrimethylammonium chloride, octadecyltrimethylammonium chloride and benzalkonium chloride;
[0024] (2) the oily organic solvent is selected from at least one of cyclohexane, cyclobutane, n-pentanol and isopropanol;
[0025] (3) The ratio of modified carbon-based microspheres to oily organic solvent is 1~2g:100~200mL;
[0026] (4) The mass ratio of modified carbon-based microspheres to cationic surfactant is 1~2:2~4;
[0027] (5) The hydrothermal reaction time is 12~20h.
[0028] In an optional embodiment, the modified carbon-based microspheres are mixed with sulfate ions, ferrous ions and sodium ions in a solution system with a pH of ≤3 to obtain a turbid solution, including:
[0029] Adding an acid solution to a solution containing ferrous sulfate and sodium sulfate, and adjusting the pH value to ≤ 3 to obtain an acid solution of mixed metal salts;
[0030] The modified carbon-based microspheres and the acid solution of the mixed metal salts are uniformly mixed to obtain a turbid solution.
[0031] In an optional embodiment, the molar concentration of sodium ions in the mixed metal salt solution is 2-6 mol / L, the molar concentration of ferrous ions is 2-4 mol / L, and the molar concentration of sulfate ions is 3-7 mol / L.
[0032] In a second aspect, the present invention provides a composite sodium iron sulfate analog positive electrode material, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0033] In a third aspect, the present invention provides a positive electrode, the active component of which includes the composite sodium iron sulfate analog positive electrode material as described in the above embodiment.
[0034] In a fourth aspect, the present invention provides a sodium ion battery comprising a positive electrode as described in the aforementioned embodiment.
[0035] The present invention has the following beneficial effects:
[0036] The preparation method provided by the embodiment of the present invention uses carbon-based microspheres with better conductivity as a template, and uses a modifier with chelating ability for ferrous ions to chelate part of the ferrous ions in the solution system to the carbon-based microspheres. The ferrous ions chelated on the carbon-based microspheres react with sulfate ions, sodium ions and water during the hydrothermal reaction, thereby forming a coating layer of sodium ferric sulfate analogs on the surface of the carbon-based microspheres, and the modifier with chelating ability for ferrous ions is present in the positive electrode material, so that the positive electrode material has the ability to capture ferrous ions, which can effectively avoid the dissolution of the positive electrode material under high voltage conditions. An emulsion is formed during the preparation process, and an oil-in-water microemulsion droplet structure of carbon-based microspheres, sulfate ions, ferrous ions and sodium ions is dispersed in the emulsion, which can ensure that even if the sphericity of the carbon-based microspheres as the template is not high enough, a positive electrode material with better sphericity can still be obtained in the end. The preparation method is simple, does not require sintering, and can produce a positive electrode material with good performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1 of the present invention;
[0039] Figure 2 This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0041] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0042] The method for preparing the composite sodium iron sulfate analog positive electrode material provided in the embodiment of the present invention comprises:
[0043] Obtaining modified carbon-based microspheres, wherein the modified carbon-based microspheres are carbon-based microspheres loaded with a modifier having chelating ability for ferrous ions;
[0044] The modified carbon-based microspheres are mixed with sulfate ions, ferrous ions and sodium ions in a solution system with a pH of ≤ 3 to obtain a turbid solution;
[0045] The turbid liquid is mixed with a cationic surfactant and an oily organic solvent to obtain an emulsion, and then the emulsion is subjected to a hydrothermal reaction at 130-160° C. to allow sulfate ions, ferrous ions and sodium ions to fully react to generate sodium ferric sulfate that is coated on the surface of the modified carbon-based microspheres;
[0046] extracting a solid product from the mixed system after the hydrothermal reaction is completed;
[0047] The boiling point of the modifier is higher than the temperature of the hydrothermal reaction;
[0048] The carbon-based microspheres are activated carbon microspheres, and the specific surface area of the carbon-based microspheres is 500-1000 m 2 / g.
[0049] The preparation method provided by the embodiment of the present invention uses carbon-based microspheres with better conductivity as a template, and uses a modifier with chelating ability for ferrous ions to chelate part of the ferrous ions in the solution system to the carbon-based microspheres. The ferrous ions chelated on the carbon-based microspheres react with sulfate ions, sodium ions and water during the hydrothermal reaction, thereby forming a coating layer of sodium ferric sulfate analogs on the surface of the carbon-based microspheres, and the modifier with chelating ability for ferrous ions is present in the positive electrode material, so that the positive electrode material has the ability to capture ferrous ions, which can effectively avoid the dissolution of the positive electrode material under high voltage conditions. An emulsion is formed during the preparation process, and an oil-in-water microemulsion droplet structure of carbon-based microspheres, sulfate ions, ferrous ions and sodium ions is dispersed in the emulsion, which can ensure that even if the sphericity of the carbon-based microspheres as the template is not high enough, a positive electrode material with better sphericity can still be obtained in the end. The preparation method is simple, does not require sintering, and can produce a positive electrode material with good performance.
[0050] The preparation method is specifically as follows:
[0051] S1. Preparation of modified carbon-based microspheres
[0052] Commercial carbon-based materials were purchased, crushed to a particle size of 5 μm using a pulverizer and an ultrasonic pulverizer, and further spheroidized using a planetary ball mill. After sieving, carbon-based microspheres of 2 to 3 μm were obtained.
[0053] The modifier is dissolved in a solvent to obtain a modifier solution, and the activated carbon microspheres are added to the modifier solution, stirred and mixed for about 1 hour, and allowed to stand for about 30 minutes, so that the modifier in the solution is adsorbed on the surface and pores of the activated carbon microspheres. Solid-liquid separation is performed to obtain modified carbon-based microspheres.
[0054] Typically, in order to ensure that a sufficient amount of the modifier is adsorbed on the carbon-based microspheres, the modifier solution contains an excess of the modifier, and the amount of the modifier solution used is based on the amount of the carbon-based microspheres that can be completely immersed. Optionally, the concentration of the modifier is 1 to 5 g / mL (e.g., 1 g / mL, 3 g / mL, or 5 g / mL).
[0055] Optionally, the carbon-based material is activated carbon, which has high electrical conductivity, high specific surface area and good adsorption capacity for the modifier.
[0056] Optionally, in order to make the carbon base have better adsorption performance for the modifier, its specific surface area is 500~1000m 2 / g (e.g. 500m 2 / g、800m 2 / g or 1000m 2 / g).
[0057] Optionally, the modifier has a group capable of chelating ferrous ions, and the group includes but is not limited to at least one of cyano, thiazole, amine and imidazole.
[0058] In addition to the ability to chelate ferrous ions, the above groups also have the ability to neutralize water acid in the material, stabilize the acid-base characteristics of the battery, and effectively improve the uneven deposition problem of sodium dendrites. Therefore, when the modifier is a modifier with the above groups, it can reduce Fe 3+ It can reduce the deposition and deterioration of SEI film at the negative electrode and reduce gas evolution.
[0059] Optionally, the modifier includes but is not limited to at least one of cimetidine, thiazolidine and nizatidine. These modifiers have a high boiling point and will not volatilize in the subsequent hydrothermal reaction. These modifiers are slightly soluble or insoluble in water, which can effectively avoid being re-dissolved in the solution system in the subsequent preparation process, and can also avoid being washed away in the water washing process after the subsequent product is obtained.
[0060] Optionally, the solvent is selected from at least one of diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate.
[0061] S2. Preparation of turbid liquid
[0062] Ferrous sulfate and sodium sulfate are dissolved in water, and then an acid solution is added thereto to adjust the pH value to ≤ 3 to obtain an acid solution of a mixed metal salt. The purpose of this step is mainly to obtain an acid solution of a mixed metal salt having a target concentration of ferrous ions, sodium ions and sulfate ions. The salt dissolved in the water may not be all sulfates. For example, chlorides, nitrates, etc. may be added. Ultimately, as long as the target concentration of ferrous ions, sodium ions and sulfate ions is met in the solution, it will be sufficient.
[0063] The modified carbon-based microspheres are mixed evenly with the acid solution of mixed metal salts, so that part of the ferrous ions in the solution are complexed on the modified carbon-based microspheres to obtain a turbid solution.
[0064] Optionally, the acid solution used to adjust the pH is a sulfuric acid solution.
[0065] Optionally, the molar concentration of the mixed metal salt solution is 2-6 mol / L (e.g., 2 mol / L, 4 mol / L or 6 mol / L), the molar concentration of ferrous ions is 2-4 mol / L (e.g., 2 mol / L, 3 mol / L or 4 mol / L), and the molar concentration of sulfate ions is 3-7 mol / L (e.g., 3 mol / L, 5 mol / L or 7 mol / L).
[0066] S3. Prepare emulsion
[0067] The cationic surfactant and the oily organic solvent are mixed uniformly to obtain an organic mixed liquid;
[0068] The organic mixed liquid and the turbid liquid were mixed and stirred for about 1 hour to obtain an emulsion.
[0069] Optionally, the cationic surfactant is selected from at least one of dodecyltrimethylammonium chloride, octadecyltrimethylammonium chloride and benzalkonium chloride.
[0070] Optionally, the oily organic solvent is selected from at least one of cyclohexane, cyclobutane, n-pentanol and isopropanol.
[0071] Optionally, to ensure that the prepared positive electrode material has a better particle size, a more suitable sodium iron sulfate analog coating layer, and a ratio of the modified carbon-based microspheres to the oily organic solvent is 1~2g:100~200mL (e.g., 1g:200mL, 1.5g:150mL or 2g:100mL).
[0072] Optionally, in order to make the components in the turbid liquid dispersed evenly and obtain a positive electrode material with good morphology, the mass ratio of the modified carbon-based microspheres to the cationic surfactant is 1~2:2~4 (for example, 1:4, 1:2, 2:2).
[0073] S4. Hydrothermal reaction
[0074] The emulsion is placed in a hydrothermal reactor, and the temperature of the hydrothermal reactor is raised to 130-160° C. (e.g., 130° C., 140° C., 150° C., or 160° C.) for hydrothermal reaction. Optionally, to ensure sufficient reaction, the reaction time is 12-20 hours (e.g., 12 hours, 15 hours, 18 hours, or 20 hours).
[0075] After the hydrothermal reaction is completed, a solid product is obtained by filtration, and the solid product is washed with clean water for multiple times, and then dried at 98-100° C. to obtain a composite sodium iron sulfate analog positive electrode material.
[0076] When a solvent with a boiling point lower than 130°C (such as diethyl carbonate) is selected as the solvent for dissolving the modifier, during the hydrothermal reaction, the diethyl carbonate adsorbed in the modified carbon-based microspheres volatilizes to generate bubbles, thereby forming a porous structure on the generated sodium iron sulfate analog coating layer, thereby increasing the specific surface area of the prepared positive electrode material.
[0077] The composite sodium iron sulfate analog positive electrode material provided in the embodiment of the present invention is prepared by the preparation method provided in the embodiment of the present invention.
[0078] The positive electrode provided by the embodiment of the present invention has an active component comprising the composite sodium iron sulfate analog positive electrode material provided by the embodiment of the present invention.
[0079] The sodium ion battery provided by the embodiment of the present invention includes the positive electrode provided by the embodiment of the present invention.
[0080] Example 1
[0081] Dissolve 1 g of cimetidine, 1 g of thiazolidine and 1 g of nizatidine in 10 mL of diethyl carbonate to obtain a modifier solution;
[0082] The specific surface area is 1000m 2 20 g of activated carbon microspheres with a volume of 100 g / g were added to the above modifier solution, stirred and mixed for 1 h, allowed to stand for 30 min, and then filtered to obtain modified carbon-based microspheres;
[0083] Dissolve sodium sulfate and ferrous sulfate in water, adjust the pH to 2.5 with sulfuric acid, and obtain a mixed metal salt acid solution with a sodium ion molar concentration of 4 mol / L, a ferrous ion molar concentration of 3 mol / L, and a sulfate ion molar concentration of 5 mol / L;
[0084] 4 g of modified carbon-based microspheres were added to 50 mL of the mixed metal salt acid solution and mixed evenly to obtain a turbid solution;
[0085] 4 g of dodecyltrimethylammonium chloride and 200 mL of cyclohexane were mixed to obtain an organic mixed solution;
[0086] The turbid liquid and the organic mixed liquid are mixed evenly to obtain an emulsion;
[0087] The emulsion was placed in a hydrothermal reactor, the temperature of the hydrothermal reactor was increased to 150°C, the reaction was carried out for 15 hours, and then filtered. The obtained solid matter was washed with pure water for 3 times, and then dried at 98°C to obtain a composite sodium iron sulfate analog positive electrode material.
[0088] Take a SEM picture of the prepared positive electrode material, such as Figure 1 As shown in the figure, it can be seen that the prepared positive electrode material has a higher sphericity and a more porous structure on the surface.
[0089] Example 2
[0090] Dissolve 3 g of cimetidine in 10 mL of diethyl carbonate to obtain a modifier solution;
[0091] The specific surface area is 500m 2 20 g of activated carbon microspheres with a volume of 1000 g / g were added to the above modifier solution, stirred and mixed for 1 hour, allowed to stand for 30 minutes, and then filtered to obtain modified carbon-based microspheres;
[0092] Dissolve sodium sulfate and ferrous sulfate in water, adjust the pH to 3 with sulfuric acid, and obtain a mixed metal salt acid solution with a sodium ion molar concentration of 6 mol / L, a ferrous ion molar concentration of 4 mol / L, and a sulfate ion molar concentration of 7 mol / L;
[0093] Add 2 g of modified carbon-based microspheres to 50 mL of the mixed metal salt acid solution and mix well to obtain a turbid solution;
[0094] 8 g of dodecyltrimethylammonium chloride and 200 mL of cyclohexane were mixed to obtain an organic mixed solution;
[0095] The turbid liquid and the organic mixed liquid are mixed evenly to obtain an emulsion;
[0096] The emulsion was placed in a hydrothermal reactor, the temperature of the hydrothermal reactor was increased to 130°C, the reaction was carried out for 20 hours, and then filtered. The obtained solid matter was washed with pure water for 3 times, and then dried at 98°C to obtain a composite sodium iron sulfate analog positive electrode material.
[0097] Example 3
[0098] Dissolve 3 g of thiazolidine in 10 mL of diethyl carbonate to obtain a modifier solution;
[0099] The specific surface area is 1000m 2 20 g of activated carbon microspheres with a volume of 1000 g / g were added to the above modifier solution, stirred and mixed for 1 hour, allowed to stand for 30 minutes, and then filtered to obtain modified carbon-based microspheres;
[0100] Dissolve sodium sulfate and ferrous sulfate in water, adjust the pH to 2.0 with sulfuric acid, and obtain a mixed metal salt acid solution with a sodium ion molar concentration of 2 mol / L, a ferrous ion molar concentration of 2 mol / L, and a sulfate ion molar concentration of 3 mol / L;
[0101] Add 3 g of modified carbon-based microspheres to 50 mL of the mixed metal salt acid solution and mix well to obtain a turbid solution;
[0102] 6 g of dodecyltrimethylammonium chloride and 300 mL of isopropanol were mixed to obtain an organic mixed solution;
[0103] The turbid liquid and the organic mixed liquid are mixed evenly to obtain an emulsion;
[0104] The emulsion was placed in a hydrothermal reactor, the temperature of the hydrothermal reactor was increased to 160°C, the reaction was carried out for 12 hours, and then filtered. The obtained solid matter was washed with pure water for 3 times, and then dried at 98°C to obtain a composite sodium iron sulfate analog positive electrode material.
[0105] Example 4
[0106] Dissolve 3 g of thiazolidine in 10 mL of diethyl carbonate to obtain a modifier solution;
[0107] The specific surface area is 1000m 2 20 g of activated carbon microspheres with a volume of 1000 g / g were added to the above modifier solution, stirred and mixed for 1 hour, allowed to stand for 30 minutes, and then filtered to obtain modified carbon-based microspheres;
[0108] Dissolve sodium sulfate and ferrous sulfate in water, adjust the pH to 3 with sulfuric acid, and obtain a mixed metal salt acid solution with a sodium ion molar concentration of 6 mol / L, a ferrous ion molar concentration of 4 mol / L, and a sulfate ion molar concentration of 7 mol / L;
[0109] Add 3 g of modified carbon-based microspheres to 50 mL of the mixed metal salt acid solution and mix well to obtain a turbid solution;
[0110] Mix 6 g of benzalkonium chloride and 300 mL of n-pentanol to obtain an organic mixed solution;
[0111] The turbid liquid and the organic mixed liquid are mixed evenly to obtain an emulsion;
[0112] The emulsion was placed in a hydrothermal reactor, the temperature of the hydrothermal reactor was increased to 160°C, the reaction was carried out for 12 hours, and then filtered. The obtained solid matter was washed with pure water for 3 times, and then dried at 98°C to obtain a composite sodium iron sulfate analog positive electrode material.
[0113] Example 5
[0114] Dissolve 3 g of nizatidine in 50 mL of diethyl carbonate to obtain a modifier solution;
[0115] The specific surface area is 500m 2 20 g of activated carbon microspheres with a volume of 1000 g / g were added to the above modifier solution, stirred and mixed for 1 hour, allowed to stand for 30 minutes, and then filtered to obtain modified carbon-based microspheres;
[0116] Dissolve sodium sulfate and ferrous sulfate in water, adjust the pH to 2.0 with sulfuric acid, and obtain a mixed metal salt acid solution with a sodium ion molar concentration of 2 mol / L, a ferrous ion molar concentration of 2 mol / L, and a sulfate ion molar concentration of 3 mol / L;
[0117] 4 g of modified carbon-based microspheres were added to 50 mL of the mixed metal salt acid solution and mixed evenly to obtain a turbid solution;
[0118] 4 g of octadecyltrimethylammonium chloride and 400 mL of cyclobutane were mixed to obtain an organic mixed solution;
[0119] The turbid liquid and the organic mixed liquid are mixed evenly to obtain an emulsion;
[0120] The emulsion was placed in a hydrothermal reactor, the temperature of the hydrothermal reactor was increased to 140°C, the reaction was carried out for 12 hours, and then filtered. The obtained solid matter was washed with pure water for 3 times, and then dried at 98°C to obtain a composite sodium iron sulfate analog positive electrode material.
[0121] Comparative Example 1
[0122] This comparative example is basically the same as Example 1, except that no oily organic solvent is added during the entire reaction process, that is, the turbid liquid is directly mixed with dodecyltrimethylammonium chloride and then subjected to a hydrothermal reaction.
[0123] Take a SEM picture of the prepared positive electrode material, such as Figure 2 As shown, Figure 2 and Figure 1 By comparison, it can be seen that the sphericity of the positive electrode material prepared in this comparative example is worse than that in Example 1, and the uniformity of the surface sodium iron sulfate analogue is also relatively poor.
[0124] Comparative Example 2
[0125] This comparative example is basically the same as Example 1, except that no cationic surfactant is added during the entire reaction process, that is, the turbid liquid is directly mixed with the oily organic solvent and then subjected to a hydrothermal reaction.
[0126] Experimental example
[0127] The positive electrode materials prepared in each embodiment and comparative example are coated with a synthetic active material oil system formula to form a positive electrode sheet. The specific method for preparing the positive electrode sheet is: using N-methylpyrrolidone as a solvent, the solid material composition is the above positive electrode material, PVDF (polyvinylidene chloride), SP (carbon black) and PVP (polyvinyl pyrrolidone), and the mass ratio of the positive electrode material, PVDF, SP and PVP is (100:7:10:3) and coated on a carbon-coated aluminum foil;
[0128] The negative electrode is made of a hard carbon water-based formula coated on a negative electrode sheet. The specific preparation method of the negative electrode sheet is as follows: using water as a solvent, the solid material composition is hard carbon, SP (carbon black), SBR (styrene butadiene rubber) and CMC (sodium carboxymethyl cellulose), the mass ratio of hard carbon, SP, SBR and CMC is 90:3:5:2, and the negative electrode sheet is coated on a carbon-coated aluminum foil;
[0129] The diaphragm is made of polypropylene;
[0130] The electrolyte selected was 1M sodium salt (sodium hexafluorophosphate) + ester solvent [EC (ethylene carbonate) 40%vt + DMC (diethyl carbonate) 60%vt] to prepare a laminated 5Ah soft-pack battery.
[0131] Each embodiment and comparative example was tested for 0.1C / 0.1C charge / discharge capacity, first coulomb efficiency, capacity retention rate at 5C rate, capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge, gas production after 100 cycles of 0.1C / 0.1C charge / discharge, and capacity retention rate after 300 cycles of 0.5C / 1C high temperature (45°C). The test results are recorded in Table 1.
[0132] Table 1 Electrochemical properties of the batteries prepared in the examples and comparative examples
[0133]
[0134] It can be seen from Table 1 that the positive electrode material prepared in the embodiment of the present invention has better electrochemical performance after being assembled into a battery.
[0135] Comparing Example 1 with Comparative Example 1, the capacity and cyclability of Comparative Example 1 are relatively poor, indicating that since no oily organic solvent is added during the preparation process of Comparative Example 1, no oil-in-water microemulsion structure is formed in the solution, and the microstructure of the prepared positive electrode material is poor, resulting in relatively poor capacity and cyclability;
[0136] Comparing Example 1 with Comparative Example 2, the capacity and cyclability of Comparative Example 2 are relatively poor, which indicates that since no cationic surfactant is added during the preparation process of Comparative Example 2, the microstructure of the prepared positive electrode material is poor, resulting in relatively poor capacity and cyclability.
[0137] In summary, the preparation method of the composite sodium ferric sulfate analog positive electrode material provided by the present invention uses carbon-based microspheres with better conductivity as a template, and uses a modifier with chelating ability for ferrous ions to chelate part of the ferrous ions in the solution system to the carbon-based microspheres. The ferrous ions chelated on the carbon-based microspheres react with sulfate ions, sodium ions and water during the hydrothermal reaction, thereby forming a coating layer of sodium ferric sulfate analogs on the surface of the carbon-based microspheres, and the modifier with chelating ability for ferrous ions is present in the positive electrode material, so that the positive electrode material has the ability to capture ferrous ions, which can effectively avoid the dissolution of the positive electrode material under high voltage conditions. In the preparation process, an emulsion is formed, and the oil-in-water microemulsion droplet structure of the carbon-based microspheres, sulfate ions, ferrous ions and sodium ions is dispersed in the emulsion, which can ensure that even if the sphericity of the carbon-based microspheres used as the template is not high enough, a positive electrode material with better sphericity can still be obtained in the end.
[0138] Therefore, the composite sodium ferric sulfate analog positive electrode material prepared by the preparation method provided by the present invention has better conductivity and the ability to capture ferrous ions, so that the battery has excellent cycle performance and specific capacity. When the modifier is selected to have a group with chelating ability for ferrous ions, and the group is selected from at least one of cyano, thiazole, amine and imidazole, in addition to making the positive electrode material have the ability to chelate ferrous ions, it also has the characteristic of being able to stabilize the acidity and alkalinity in the battery, and can effectively improve the problem of uneven deposition of sodium dendrites.
[0139] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite sodium iron sulfate analog positive electrode material, characterized in that: include: Obtaining modified carbon-based microspheres, wherein the modified carbon-based microspheres are carbon-based microspheres loaded with a modifier having chelating ability for ferrous ions; The modified carbon-based microspheres are mixed with sulfate ions, ferrous ions and sodium ions in a solution system with a pH of ≤3 to obtain a turbid solution; The turbid liquid is mixed with a cationic surfactant and an oily organic solvent to obtain an emulsion, and then the emulsion is subjected to a hydrothermal reaction at 130-160° C. to allow sulfate ions, ferrous ions and sodium ions to fully react to generate sodium ferric sulfate to be coated on the surface of the modified carbon-based microspheres; extracting a solid product from the mixed system after the hydrothermal reaction is completed; The boiling point of the modifier is higher than the temperature of the hydrothermal reaction; The carbon-based microspheres are activated carbon microspheres, and the specific surface area of the carbon-based microspheres is 500-1000 m 2 / g; The modifier has a group capable of chelating ferrous ions, and the group is selected from at least one of cyano, thiazole, amine and imidazole; or, the modifier is selected from at least one of cimetidine, thiazolidine and nizatidine.
2. The preparation method according to claim 1, characterized in that: The method for obtaining the modified carbon-based microspheres comprises: The modifier is dissolved in a solvent to obtain a modifier solution, and the carbon-based microspheres are immersed in the modifier solution so that the modifier is adsorbed on the carbon-based microspheres; then, solid-liquid separation is performed to obtain the modified carbon-based microspheres.
3. The preparation method according to claim 2, characterized in that: Includes at least one of the following features (1) to (3): (1) The particle size of the carbon-based microspheres is 2-3 μm; (2) The concentration of the modifier solution is 1-5 g / mL; (3) The solvent for dissolving the modifier is at least one selected from diethyl carbonate, dimethyl carbonate and ethyl methyl carbonate.
4. The preparation method according to claim 1, characterized in that: Includes at least one of the following features (1) to (5): (1) The cationic surfactant is at least one selected from the group consisting of dodecyltrimethylammonium chloride, octadecyltrimethylammonium chloride and benzalkonium chloride; (2) The oily organic solvent is selected from at least one of cyclohexane, cyclobutane, n-pentanol and isopropanol; (3) The ratio of the modified carbon-based microspheres to the oily organic solvent is 1-2 g: 100-200 mL; (4) The mass ratio of the modified carbon-based microspheres to the cationic surfactant is 1-2:2-4; (5) The hydrothermal reaction time is 12~20h.
5. The preparation method according to claim 1, characterized in that: The method of mixing the modified carbon-based microspheres with sulfate ions, ferrous ions and sodium ions in a solution system with a pH of ≤3 to obtain a turbid solution includes: Adding an acid solution to a solution containing ferrous sulfate and sodium sulfate, and adjusting the pH value to ≤ 3 to obtain an acid solution of mixed metal salts; The modified carbon-based microspheres and the acid solution of the mixed metal salts are uniformly mixed to obtain a turbid solution.
6. The preparation method according to claim 5, characterized in that: The molar concentration of sodium ions in the mixed metal salt solution is 2-6 mol / L, the molar concentration of ferrous ions is 2-4 mol / L, and the molar concentration of sulfate ions is 3-7 mol / L.
7. A composite sodium iron sulfate analog positive electrode material, characterized in that: The method is prepared according to any one of claims 1 to 6.
8. A positive electrode, characterized in that Its active ingredients include the composite sodium iron sulfate analog positive electrode material as claimed in claim 7.
9. A sodium ion battery, characterized in that: Comprising the positive electrode as claimed in claim 8.
Citation Information
Patent Citations
Sodium ferrous sulfate / graphene composite positive electrode material for sodium ion battery, and preparation method thereof
CN106848236A
Composite sodium ferric sulfate positive electrode material and preparation method thereof, positive electrode and sodium ion battery
CN116779808A